2019
DOI: 10.3390/jcm9010046
|View full text |Cite
|
Sign up to set email alerts
|

Favorable 90-Day Mortality in Obese Caucasian Patients with Septic Shock According to the Sepsis-3 Definition

Abstract: Septic shock is a frequent life-threatening condition and a leading cause of mortality in intensive care units (ICUs). Previous investigations have reported a potentially protective effect of obesity in septic shock patients. However, prior results have been inconsistent, focused on short-term in-hospital mortality and inadequately adjusted for confounders, and they have rarely applied the currently valid Sepsis-3 definition criteria for septic shock. This investigation examined the effect of obesity on 90-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…For the purpose of the present study, we prospectively enrolled 707 consecutive patients with clinically defined sepsis from three surgical intensive care units (ICUs) at the University Medical Center Goettingen, Germany, since 2012. Our cohort of sepsis patients, or significant proportions of it, were previously studied in other published investigations for other clinical and experimental research questions by our study group [14][15][16]21,24,25,43]. Patient screening for sepsis and study recruitment was performed by study physicians on a daily basis using the currently valid international sepsis definitions and guidelines [1,[44][45][46].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of the present study, we prospectively enrolled 707 consecutive patients with clinically defined sepsis from three surgical intensive care units (ICUs) at the University Medical Center Goettingen, Germany, since 2012. Our cohort of sepsis patients, or significant proportions of it, were previously studied in other published investigations for other clinical and experimental research questions by our study group [14][15][16]21,24,25,43]. Patient screening for sepsis and study recruitment was performed by study physicians on a daily basis using the currently valid international sepsis definitions and guidelines [1,[44][45][46].…”
Section: Patientsmentioning
confidence: 99%
“…Diagnostic procedures, pathogen characteristics and antibiotic treatment strategies are exogenous factors, for instance [10,11]. Endogenous factors include preexisting conditions and chronic diseases, host immune status, genetic predisposition, age, gender, and many more [12][13][14][15]. The exploration and investigation of the genetic determinants of sepsis as well as inflammatory conditions in general is a popular method, that could be extensively applied in the future [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…One population-based analysis of a Spanish hospital discharge database published in this Special Issue revealed that, even in the young study population (aged 20–44 years), the in-hospital sepsis mortality was 24% (2006–2015) and associated with age, comorbidity, and the extent of organ dysfunction [ 2 ]. One metabolic disease with a dramatically increasing prevalence in the first world is obesity, which was analyzed in regard to its impact on sepsis survival by Mewes et al [ 3 ]. Despite the negative long-term effects of obesity, such as the development of arterial hypertension, diabetes mellitus, etc., interestingly, there seems to be a protective effect of obesity on sepsis survival.…”
Section: Epidemiology Of Sepsis (Three Publications)mentioning
confidence: 99%
“…Despite the negative long-term effects of obesity, such as the development of arterial hypertension, diabetes mellitus, etc., interestingly, there seems to be a protective effect of obesity on sepsis survival. Obese patients (body mass index > 30 kg/m 2 ) showed decreased 90-day mortality in the Caucasian study group [ 3 ].…”
Section: Epidemiology Of Sepsis (Three Publications)mentioning
confidence: 99%
“…Z problematiky paradoxu obezity jsou zajímavé práce, které pro kazují nižší mortalitu obézních po sepsi (10). Je přitom známo, že po septických stavech a infekcích výrazně stoupá riziko kardiovaskulárních příhod obecně (11).…”
Section: Novinky V Epidemiologii a Patogenezi Kardiovaskulárních Onemocnění U Obézníchunclassified